Shaking the Tree: Multi-locus Sequence Typing Usurps Current Onchocercid (Filarial Nematode) Phylogeny. - Emilie Lefoulon; Odile Bain; Jérôme Bourret; Kerstin Junker; Ricardo Guerrero; Israel Cañizales; Yuriy Kuzmin; Tri Baskoro T Satoto; Jorge Manuel Cardenas-Callirgos; Sueli de Souza Lima; Christian Raccurt; Yasen Mutafchiev; et al. (Public Library of Science (PLoS), 2015)
During the past twenty years, a number of molecular analyses have been performed to determine the evolutionary relationships of Onchocercidae, a family of filarial nematodes encompassing several species of medical or veterinary importance. However, opportunities for broad taxonomic sampling have been scarce, and analyses were based mainly on 12S rDNA and coxI gene sequences. While being suitable for species differentiation, these mitochondrial genes cannot be used to infer phylogenetic hypotheses at higher taxonomic levels. In the present study, 48 species, representing seven of eight subfamilies within the Onchocercidae, were sampled and sequences of seven gene loci (nuclear and mitochondrial) analysed, resulting in the hitherto largest molecular phylogenetic investigation into this family. Although our data support the current hypothesis that the Oswaldofilariinae, Waltonellinae and Icosiellinae subfamilies separated early from the remaining onchocercids, Setariinae was recovered as a well separated clade. Dirofilaria, Loxodontofilaria and Onchocerca constituted a strongly supported clade despite belonging to different subfamilies (Onchocercinae and Dirofilariinae). Finally, the separation between Splendidofilariinae, Dirofilariinae and Onchocercinae will have to be reconsidered.